Movie, Writing, and Character Education: A Study on an EFL Writing Class - Dian Safitri; Nur Rosita; Rita Arni (Universitas Negeri Padang, 2023)
This paper is a one-shot case study which aims to reveal if the integration of anti-drug character education into foreign language writing classes by using short movie is effective to achieve both the learning and character education objectives. An online writing test and a four-Likert scale questionnaire with twenty close-ended questions were given to 32 English college students in West Sumatra. The data of students’ writing were analyzed quantitatively by using Wilcoxon Match Pair Test, while that of the questionnaire was analyzed by using Mann Whitney U Test. The analysis outputs show the success of the integration by the following results: (1) there is a significant improvement in word production number (Asymp. Sign (2-tailed)=0.000); (2) there is a significant improvement in writing score (Asymp. Sign (2-tailed)=0.000); and (3) the students’ understanding towards the moral values sent by the movie are excellent (M=3.92). The findings may have pedagogical implications in adding an effective media reference to improve students’ writing skill and to integrate character education into EFL learning.